The Role of Internal Audit, Fraud Prevention, and Detection, on Public Sector Financial Performance (Empirical Study at District Councils, Sierra Leone) - Conteh, Abdul; Bawono, Andy Dwi Bayu; Sasongko, Noer (PT FORMOSA CENDEKIA GLOBAL, 2024)
This empirical study investigates the role of internal audit, fraud prevention, and detection on public sector financial performance in Sierra Leone, specifically focusing on district councils. The research aims to determine the impact of fraud prevention, detection on public sector financial performance and provides recommendations for enhancing financial management practices in the public sector. Using quantitative methodology, data was collected through a google form questionnaire from internal auditors and finance officers in Bo, Bonthe, Moyamba, and Pujehun District Councils in the Southern Province of Sierra Leone. The study used SPSS 26 to analyze the influence of internal audit, fraud prevention, fraud detection on financial performance. The results indicate that internal audits have a positive impact on public sector financial performance in Sierra Leone District Councils. However, the study found that fraud prevention does not significantly influence financial performance. On the other hand, effective fraud detection mechanisms positively impacted financial performance.